Green Tea Extract Increases The Number of Granulosa Cells and E2 Serum Levels of Female Rats Exposed by Cypermethrin - Laili, Fitria Jannatul; Winarsih, Sri; Mintaroem, Karyono (Health Notions, 2018)
processing